EPA’S DEFINITION OF “SOLID WASTE” UNDER SUBTITLE C OF THE RESOURCE CONSERVATION AND RECOVERY ACT: IS EPA ADEQUATELY PROTECTING HUMAN HEALTH AND THE ENVIRONMENT WHILE PROMOTING RECYCLING? (Utah Environmental Law Review, 2010)
Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} An industrial or other business facility that generates hazardous secondary materials may seek to recover valuable parts of these materials, either to re-use them as raw materials or feedstock in the facility's production process or to sell them as a by-product (sometimes after removal of contaminants). Such a facility may seek to do so to increase the facility's profits by increasing the facility's sales, by reducing the facility's expenditures for raw materials and by avoiding stringent and expensive Environmental Protection Agency (EPA) regulations under Subtitle C of the federal Resource Conservation and Recovery Act (RCRA or "the Act"). Subtitle C would regulate the facility's treatment, storage, and disposal of the secondary materials if they were classified as hazardous waste under the Act. Since the enactment of RCRA in 1976, EPA has struggled with the definition and criteria it should use in determining when a hazardous secondary recycled material is a "hazardous waste" subject to regulation under Subtitle C of RCRA. EPA has changed its position on this issue numerous times during this period. As discussed in more detail later in this Introduction, this article examines the interpretation of "solid waste" under Subtitle C of RCRA by both EPA and the courts; it also examines the evolution of EPA regulations under Subtitle C of RCRA, which define when particular recycled hazardous secondary materials will be excluded from the Subtitle C regulations applicable to hazardous solid wastes.